If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -162 = 9x + 46 Reorder the terms: -162 + -7x = 9x + 46 Reorder the terms: -162 + -7x = 46 + 9x Solving -162 + -7x = 46 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -162 + -7x + -9x = 46 + 9x + -9x Combine like terms: -7x + -9x = -16x -162 + -16x = 46 + 9x + -9x Combine like terms: 9x + -9x = 0 -162 + -16x = 46 + 0 -162 + -16x = 46 Add '162' to each side of the equation. -162 + 162 + -16x = 46 + 162 Combine like terms: -162 + 162 = 0 0 + -16x = 46 + 162 -16x = 46 + 162 Combine like terms: 46 + 162 = 208 -16x = 208 Divide each side by '-16'. x = -13 Simplifying x = -13
| 5(m+3)=2(3m+1) | | (94)=136 | | 3x^2-x+7=0 | | -91-9x=-3x+35 | | -112+128x-16x^2=0 | | 4x+11y=3 | | (49)=70 | | -20-3x=28+x | | (70)=49 | | 8x-48=5x+33 | | (55)=110 | | -20x+10y=50 | | -80-5x=112+7x | | -6x-161=7x+47 | | -25=q-.2q^2 | | 25q=.2q^2 | | -1.6=4.8+1.6x | | -3x+14=0 | | x+0.2=0.4x+3.2 | | 8d+4d-5d-8-5d=0 | | -4a+2=-8-14 | | 6(m+3)+m+12=0 | | n-8=-11 | | -2.4=-1.5x-1.7 | | 5x^2-12x^2+7=0 | | 3x+.63-2x-.25=.63 | | 820-71= | | 2.5s-2+3(s-11)=50 | | 25s-2+3(s-11)=50 | | -2(3+4x)=18 | | -49+f=9 | | w^2-10w+15=0 |